Analysis of H-bonded molecular association in formamide with alcohols. (2022) - Kumar Singh, Raj; Misra, Amit; Malik, Monika; Singh, Manvinder; Gupta, Manisha
Abstract: Ultrasonic velocity, density, viscosity, and refractive index have been measured in binary liquid mixtures of formamide with 1-propanol and 2-propanol at atmospheric pressure and 293 K, 303 K, and 313 K temperatures over the entire range of composition. Experimentally determined values have been used to calculate excess Gibb's free energy of activation for viscous flow 'ΔG* E ', excess internal pressure 'πi E ', and deviation in molar refraction 'ΔRm ' . All the excess and deviated functions have been plotted against the mole fraction of formamide and calculated values have been fitted to the Redlich-Kister polynomial equation. The calculated excess values or deviation parameters have been discussed on the basis of molecular association in these binary mixtures. Further, refractive index of these liquid mixtures has been predicted using various theoretical mixing rules.